CONSUMER PERCEPTION TOWARDS CASHLESS TRANSACTIONS IN MALAPPURAM DISTRICT - M, Abdurahman.; P, Baijumon; Shajithra O P (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The increasing prevalence of cashless transactions has significantly reshaped the retail sector, reflecting a broader shift towards a digital economy. This study examines consumer perceptions of cashless transactions, focusing on trust, security, convenience, and accessibility. It seeks to identify customers’ satisfaction levels with cashless payment methods while also analyzing the challenges they face. This study explores consumer perceptions of cashless payments in Malappuram District, Kerala, analyzing factors like trust, security, and accessibility. Data from 71 respondents were analyzed using statistical tools, revealing both positive consumer sentiment and concerns over security and transaction reliability. The findings emphasize the need for improved financial literacy, regulatory support, and enhanced security measures to boost consumer confidence and adoption of digital payments.